1993
DOI: 10.1002/bjs.1800800607
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of postoperative thromboembolism with low molecular weight heparins

Abstract: To evaluate the thromboprophylactic use of low molecular weight heparins (LMWHs), publications from 27 orthopaedic trials and 35 studies of patients undergoing general or gynaecological surgery were scrutinized and subjected to a partial meta-analysis. In orthopaedic surgery, LMWHs were superior to placebo or dextran and at least as efficient as unfractionated heparin in the prevention of deep vein thrombosis (DVT). Compared with unfractionated heparin, one of the LMWH preparations significantly reduced the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(71 citation statements)
references
References 57 publications
3
62
1
5
Order By: Relevance
“…23 Charnley abandoned the use of phenindione because the benefit from a reduction in the mortality rate due to pulmonary embolism was matched by an increased mortality from gastrointestinal haemorrhage. 24 Coventry et al 2 recommended postponing anticoagulation with warfarin until the fifth postoperative day, but this would have failed to prevent three of the four cases of fatal pulmonary embolism which were reported by Warwick et al 16 Meta-analysis shows that both low-dose, unfractionated and low-molecular-weight heparin substantially reduce the incidence of venographically demonstrated DVT after THR from about 45% to about 23% 25 and about 19%, 26 although with some haemorrhagic side-effects. This reduction in DVT has been extrapolated to imply a reduction in the incidence of fatal pulmonary embolism, but no study has been powerful enough to demonstrate this.…”
Section: Discussionmentioning
confidence: 99%
“…23 Charnley abandoned the use of phenindione because the benefit from a reduction in the mortality rate due to pulmonary embolism was matched by an increased mortality from gastrointestinal haemorrhage. 24 Coventry et al 2 recommended postponing anticoagulation with warfarin until the fifth postoperative day, but this would have failed to prevent three of the four cases of fatal pulmonary embolism which were reported by Warwick et al 16 Meta-analysis shows that both low-dose, unfractionated and low-molecular-weight heparin substantially reduce the incidence of venographically demonstrated DVT after THR from about 45% to about 23% 25 and about 19%, 26 although with some haemorrhagic side-effects. This reduction in DVT has been extrapolated to imply a reduction in the incidence of fatal pulmonary embolism, but no study has been powerful enough to demonstrate this.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have shown less risk of thrombocytopenia and bleeding complications with LMWH compared with unfractionated heparin. 3,4 We report the results of a prospective study designed to address the safety of LMWH used in patients undergoing radical retropubic prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In elderly people undergoing surgery for fracture of the hip, the incidence of fatal PE is probably higher than in elective surgery, at around 4%. 10,23,24 This is within the high-risk category under the THRIFT classification. Data from the PEP study, produced after this review, suggest that even after fracture of the hip the incidence of fatal PE is much lower.…”
Section: Risks and Benefits Of Prophylaxis Against Venous Thromboembomentioning
confidence: 99%